Implementasi Metode Integer Programming Untuk Penjadualan Tenaga Medis Pada Situasi Darurat Berbasis Aplikasi Mobile - Ahmad Saikhu; Laili Rochmah (IC-ITECHS, 2014)
Unexpected events, including natural disasters and disasters caused by human negligence often results in the occurrence of an emergency condition. For a disaster event, disaster mitigation is not only necessary, but an emergency response plan for handling the health / safety of life of the victims, are very important. Proper medical treatment by a professional will save many lives. Such event can occur at any location and any time, and in the same time can occur a few emergency events that require some physician team with qualified doctors / particular specialization for handling a number of victims. On the other hand, physicians have a high mobility in performing his professional duties. Due to the limited number of physicians with certain qualifications as required in an emergency and demands should arrive quickly, we need a reliable system in order to coordinate the assignment of an emergency event can be handled properly. Coordination and scheduling can be done by those who have an authority. Scheduling optimization model with special characteristics, among others the existence of a number of emergency events at several locations at the same time, the limited number of physician, needs special skills for handling emergencies, and the presence of medical personnel who are mobile can be done by developing one assignment optimization model, namely integer linear programming (ILP). As for fast communication for coordination between the management authority with a number of doctors, a mobile application can be applied. In this research, Bipartite Graph (BG) model, Ford-Fulkerson Algorithm (FFA) and IPL model as the main part of the decision making structure are implemented into a program. The first model (BG) present concordance between physicians with their expertises. The second model (FFA) helps the authority to determine physician who meet the condition. The third model (ILP) helps the authority to determine the best combination of assignment physician. Input, process, output, and feedback from the implementation is represent decision making system for the assignment physician in to the emergency events. So that the physicians can quickly find out the assignment, the schedule can be accessed through mobile applications.